Correlation between Daily Page Views and View Duration: An Exploration of National Library Websites - Mandal, Sukanya; Das, Arijit (Journal of Information and Knowledge, 2018)
Generally page view and view duration help to estimate the popularity of a site they are also determining factors for estimating the extent of use of that site. This paper seeks to establish a “correlation” between the two variables, i.e. daily page views per visitor and daily time on site (view duration) of twenty five national library websites around the world to see the degree of association. A scatter diagram indicating the nature of association between these two variables is drawn. The Pearson’s Correlation Coefficient (r) is 0.744, which indicates a strong positive relation between these two variables. The pattern of scatter diagram also represents a positive correlation, which means the association between the variables is direct, indicating thereby that if the value of average page view is high then the value of daily time on site also will be high, and low values are associated with low values.